Utilization pattern of blood and its components in a tertiary care super speciality hospital - Handa, Anjali; Bundas, Sunita; Pal, Ashok (International Journal Of Community Medicine And Public Health, 2020)
Background: Blood is the most precious gift for human life. Blood transfusion services play a vital role in managing health care services. There is no substitute for blood and its components till date, therefore blood donation drive is very crucial. The primary responsibility of blood transfusion services is to provide safe, sufficient and timely supply of blood and blood products. There has been shift for usage of blood and blood components from the use of whole blood so that maximum utilization of this precious resource could be done. Aim and objectives was to study pattern of utilization of blood and blood components in a super speciality hospital with the indications for transfusions for different components during the study period. Methods: This retrospective study for 12 months (January 2019- December 2 019) on pattern of utilization of blood components was carried out in the department of immunohaematology and transfusion medicine in a super speciality hospital. Results: There were total of 90237 transfusions which were carried out during the study period of 12 months. During the study period, 366 stored whole blood units, 55300 Packed RBC units, 19111 FFP units, 14298 Random Donor Platelet units, 1119 single donor platelets and 43 cryoprecipitate units were issued for use in patients admitted to our hospital. Conclusions: Periodic review and audit of blood component usage becomes essential to assess the blood utilization pattern in any hospital.